The Increase in the Ability to Speak through the Katumbar Media in Children Aged 3-4 Years in Kindergarten: Peningkatan Kemampuan Berbicara Melalui Media Katumbar Pada Anak Usia 3-4 Tahun di KB - Dewi Alizza Siffana; Evie Destiana (Academia Open, 2022)
Word cards pictorial of one of the media that can help the development of the ability to speak the child, because the media card images are concrete. From the observation of the researcher, the problem that often occurs in the KB Aisyiyah Bustanul Athfal 1 Candi. The ability to speak, children Play Groups yet can achieve optimal development, this is because the ability to speak the child is not smooth and less interestingly media used during the learning process takes place. Therefore it is necessary supporting media so that the kids want to reveal the experience of day - to- day, so that children become excited in following the learning and the goal of the teacher to improve the speaking skills of children can be successfully and running maximum by using the Card Word Picture. This research using the Method of Classroom Action Research to improve the ability to speak. This study was conducted in 2 cycles. The study was conducted in three stages namely pre-cycle, cycle I and cycle II to obtain the results as expected. In the pre cycle, most children still acquire an average value of 44,98% while in the first cycle the percentage value increases so that the obtained percentage value to be 63,31%, which means less than the maximum. Then the researchers proceeded to give the action in cycle II, after doing research on the second cycle is the percentage of the average value of the child becomes 81,66%, resulting from the acquisition of the average in cycle I and cycle II increased again. It can be seen from the comparison between cycle I and cycle II during the study. From the results obtained, there is an increase in proving that with the Word Cards Picture can improve the Speaking ability of the child.